Science Diplomacy: An Overview in the Global and National Context - Shrestha, Sunil B.; Parajuli, Laxmi K.; Shrestha, Marina Vaidya (Journal of Foreign Affairs, 2022)
Science Diplomacy seeks avenues for strengthening humanity and consolidating the existing inter-nation relationships through academic and industrial collaboration between nations on various scientific and technological frontiers. Science and technology are effective tools for addressing global challenges and cross-boundary disputes amicably by promoting international scientific collaboration to harness the potentials of partner countries. In this perspective, we revisit the global developments in science diplomacy and with a particular focus on Nepal, we explore how science diplomacy has been vital for establishing scientific collaborations. The paper also highlights the effort and the role played by the Nepali diaspora for enhancing scientific collaboration and technology transfer between Nepal and the scientifically advanced nations. While further strengthening diplomatic ties that Nepal currently enjoys with friends worldwide, we discuss various policy measures that can leverage scientific output in the country by encompassing scientific and technological collaboration as an integral part of foreign policy. We believe that this paper can also serve as a useful reference to achieve Sustainable Development Goals and combat global challenges such as climate change, natural disasters, and pandemics through science diplomacy and cooperation.